2020
DOI: 10.1186/s13058-020-01303-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three scoring methods using the FDA-approved 22C3 immunohistochemistry assay to evaluate PD-L1 expression in breast cancer and their association with clinicopathologic factors

Abstract: Background: In the evaluation of PD-L1 expression to select patients for anti-PD-1/PD-L1 treatment, uniform guidelines that account for different immunohistochemistry assays, different cell types and different cutoff values across tumor types are lacking. Data on how different scoring methods compare in breast cancer are scant. Methods: Using FDA-approved 22C3 diagnostic immunohistochemistry assay, we retrospectively evaluated PD-L1 expression in 496 primary invasive breast tumors that were not exposed to anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 48 publications
7
48
0
Order By: Relevance
“…A total of 22 articles were included in this study [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Most of the studies were retrospective, and the follow-up interval varied from 3 months to 15 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 22 articles were included in this study [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Most of the studies were retrospective, and the follow-up interval varied from 3 months to 15 years.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies evaluated the association between PD-L1 expression and survival in women with IBC [ 19 , 22 , 23 , 25 , 26 , 28 , 29 , 39 , 40 , 41 ] ( Table 3 ). Of these, five studies determined OS [ 22 , 28 , 29 , 39 , 40 ], and five studies evaluated DFS [ 20 , 23 , 25 , 26 , 41 ]. Of these, three studies found that PD-L1 expression was associated with OS using Kaplan–Meier curves [ 22 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the combined positive score involves both TC and IC located in the TC or the narrow rim around the TC. The number of PD-L1-positive TCs and ICs was counted, relative to the number of all vital TCs, and then multiplied by 100 [102,104]. These scoring methods were associated with the adopted clones.…”
Section: Scoring Methodsmentioning
confidence: 99%
“…Over-expression of PD-L1 in cancer is thought to co-opt this mechanism, leading to immune system evasion, one of the modern hallmarks of cancer [ 114 ]. While its expression by IHC analysis can be utilised as a biomarker in breast cancer, there is no consensus about assay choice; cut-off; or measuring tumour cells, immune cells, or both [ 115 ]. One study using modified Histo-score with a positive cut-off ≥ 100 found 23% of 650 evaluable breast cases to be PD-L1+, as well as an association with worse prognosis, both in the overall cohort and the HER2-negative luminal B subset [ 116 ].…”
Section: Histological Biomarkers In Er + Breast Cancermentioning
confidence: 99%